2016
DOI: 10.1002/ange.201509761
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Absolute Configuration of the Pseudo‐Symmetric Natural Product Elatenyne by the Crystalline Sponge Method

Abstract: Elatenyne is a marine natural product that was isolated in 1986. Despite its simple 2,2′‐bifuranyl backbone, its relative structure was only recently determined. The absolute configuration of elatenyne has still not been unequivocally confirmed because of its pseudo‐meso core structure, which results in a specific rotation, [α]D , of almost zero. In this work, the structure of natural elatenyne was determined by the crystalline sponge method and the use of a porous coordination network (a crystalline sponge) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 21 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…Others observed that enantiopure compounds can be ordered inside the host channels and give rise to loss of inversion symmetry, possibly aided by solvents. 2 , 22 , 25 27 This is indeed the case for β-pinene but we did not observe this for camphene and α-pinene. It is not clear if ordering of enantiopure compounds or of enantiomeric pairs is most common.…”
Section: Resultsmentioning
confidence: 49%
See 1 more Smart Citation
“…Others observed that enantiopure compounds can be ordered inside the host channels and give rise to loss of inversion symmetry, possibly aided by solvents. 2 , 22 , 25 27 This is indeed the case for β-pinene but we did not observe this for camphene and α-pinene. It is not clear if ordering of enantiopure compounds or of enantiomeric pairs is most common.…”
Section: Resultsmentioning
confidence: 49%
“…The porous framework introduced by Fujita and responsible for most of the crystalline sponge applications up to now has a space group that in principle is incompatible with chiral compounds. Nevertheless, successful structure determinations of several chiral compounds have been reported, 2 , 25 27 but only after guest ordering resulted in the breaking of the inversion/mirror symmetry of the host–guest system. Such symmetry breaking will not always occur, and the problems encountered during the determination of the chirality of miyakosyne A 1 demonstrate that the interplay between chiral guests and the nonchiral host is not yet sufficiently understood.…”
Section: Introductionmentioning
confidence: 99%
“…These interactions include π-π, CH-π, and charge-transfer interactions. The technique was first introduced by Fujita et al [1] in 2013 and since then has grown rapidly and proven helpful in the structure elucidation of natural products [2], [3] volatile compounds [4], [5], ozonides [6], metabolites [7], in studying reaction mechanisms [8], [9] and in absolute structure determination [10], [11]. With the success of the crystalline sponge method many researchers developed alternative crystalline sponges [12], [13].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the Fujita group has updated the methodology (Hoshino, Khutia, Xing, Inokuma, & Fujita, ). To date, most of the applications of this method to characterizing natural‐product structures were performed by the Fujita laboratory (Brkljaca et al., ; Kai, Sogame, Sakurai, Nasu, & Fujita, ; Lee, Hoshino, Fujita, & Urban, ; Matsuda et al., ; Urban, Brkljaca, Hoshino, Lee, & Fujita, ; Yoshioka, Inokuma, Hoshino, Sato, & Fujita, ), although another group has published the absolute configuration determination of a plant metabolite, asarinin, using crystalline‐sponge methods (Li, Yang, Gu, & Di, ). It has been reported that crystalline sponges could be used as an affinity matrix to trap sesquiterpenes from a crude red algal extract for analysis (Wada et al., ).…”
Section: Techniques In Natural‐product Drug Discoverymentioning
confidence: 99%